Stress concentration and buckling behaviour of shear loaded composite panels with reinforced cutouts - Guo, Shijun J. (Elsevier Science B.V., Amsterdam., 2007)
Numerical and experimental studies have been conducted to investigate the effect of reinforcements around cutouts on the stress concentration and buckling behaviour of a carbon/epoxy composite panel under in-plane shear load. Four different types of cutout reinforcements made of a range of materials were evaluated. In the analysis, finite element method and an analytical method based on the laminate theory were employed to perform parametric studies on the various reinforcement designs. Four test panels were then manufactured and tested to validate the analysis results. Good agreement was found between the analytical and test results. Based on the validated analytical models, the best cutout reinforcement was determined.
Keywords: Cutout reinforcement; Buckling; Stress concentrations; Finite element analysis